2014
DOI: 10.1007/s11033-014-3682-8
|View full text |Cite
|
Sign up to set email alerts
|

The glucose transporter 1 -GLUT1- from the white shrimp Litopenaeus vannamei is up-regulated during hypoxia

Abstract: During hypoxia the shrimp Litopenaeus vannamei accelerates anaerobic glycolysis to obtain energy; therefore, a correct supply of glucose to the cells is needed. Facilitated glucose transport across the cells is mediated by a group of membrane embedded integral proteins called GLUT; being GLUT1 the most ubiquitous form. In this work, we report the first cDNA nucleotide and deduced amino acid sequences of a glucose transporter 1 from L. vannamei. A 1619 bp sequence was obtained by RT-PCR and RACE approaches. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 64 publications
0
11
1
Order By: Relevance
“…The ORF in this study was 15 amino acid longer than that in Martínez‐Quintana's research (Martínez‐Quintana et al . ) and 66 amino acid shorter than that in Huang's study (Huang et al . ), and we found a Mos polyadenylation response element (Mos‐PRE) and Gamma‐interferon‐activated inhibitor of Ceruloplasmin mRNA translation (GAIT elements) in the 3′UTR of lvGLUT1 which was different with that sequence.…”
Section: Resultscontrasting
confidence: 54%
See 4 more Smart Citations
“…The ORF in this study was 15 amino acid longer than that in Martínez‐Quintana's research (Martínez‐Quintana et al . ) and 66 amino acid shorter than that in Huang's study (Huang et al . ), and we found a Mos polyadenylation response element (Mos‐PRE) and Gamma‐interferon‐activated inhibitor of Ceruloplasmin mRNA translation (GAIT elements) in the 3′UTR of lvGLUT1 which was different with that sequence.…”
Section: Resultscontrasting
confidence: 54%
“…He found that LvGLUT1 expressed the highest in gills, followed by pleopods, intestine, muscle, hemocytes and hepatopancreas in turn (Martínez‐Quintana et al . ). The location of the gene expression is closely related to the tissue function and metabolism (Wang et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations